The Effect Of Flores Local Content Video on Students’ Speaking Skill of SMPN 1 ENDE - Gratiana Sama; Yofita Lawe Duka; Marianus Roni (Jurnal Riset Teknologi dan Inovasi Pendidikan (Jartika), 2021)
Abstract: This study aimed at determining the effectiveness of the use of video-based on local content Flores on the speaking ability of students at SMPN 1 Ende. This research is a classroom action research with the quasi-experimental method. The results of this study indicated that the Flores Local Content Video has not affected the English speaking skill of SMP Negeri 1 Ende students because the practical learning method of speaking English does not use videos based on local content in the Flores area, but students are familiar with the implementing of English learning videos in general. The researcher hopes that this article can be useful for students and teachers as well as future researchers who will study the improvement of students' English speaking skills. The researcher also expects that English teachers can create and apply English learning videos based on local content.